Nickel nanoparticles in fullerene matrix fabricated by co-evaporation: structural, magnetic, and magneto-optical properties - Salvan, G.; Pacurariu, R.; Li, W.; Fronk, M.; Rosu, D. M.; Zahn, D. R. T.; Schubert, S.; Radons, G.; Schulze, S.; Hietschold, M.; Bachmann, Julien; Nielsch, Kornelius; et al. (Applied Physics A-Materials Science & Processing, 2011)
In this work, Ni nanoparticles embedded in fullerene matrices were fabricated by co-evaporation in ultra-high vacuum and their structural, magnetic, and electronic properties were assessed by a variety of experimental methods corroborated with theoretical simulations. The mixed Ni/fullerene films were grown on Si substrates kept at room temperature. The size of Ni nanoparticles embedded in the organic matrix was determined to be between 1.5 nm and 8 nm from high-resolution transmission electron microscopy and electron diffraction investigations. The films exhibit a complex behavior of the magnetic hysteresis curves, a combination of ferromagnetic, paramagnetic, and superparamagnetic contributions, which was modeled using a Preisach-based theoretical approach. Spectroscopic measurements of the magneto-optical Kerr effect deliver information on the electronic properties of the nanoparticles.